Older adults’ experiences with using information and communication technology and tech support services in New York City: findings and recommendations for post-pandemic digital pedagogy for older adults - Finkelstein, Ruth; Wu, Yiyi; Brennan-Ing, Mark (Frontiers in Psychology, 2023)
Introduction Although Information and Communication Technology (ICT) has great potential to help older adults cope with challenges associated with aging, the intended benefits of ICT are not always realized in this population due to access barriers and low digital literacy. During the COVID-19 pandemic, numerous tech support initiatives for older adults got underway. However, evaluation of the effectiveness of these initiatives is less common. This research partnered with a large, multi-service organization in New York City that gave some groups of their clients ICT devices, unlimited broadband, and access to technology training in response to COVID-19 lockdowns. This study investigates older adults’ experiences with ICT and ICT support services to better inform the existing and emerging tech support for older adults during and beyond the pandemic. Methods Data were obtained from interviewer-administered surveys of 35 older adult recipients of ICT devices, connectivity, and training in New York City. The average age was 74 years (range = 55–90 years). The group was diverse regarding race/ethnicity (Black 29%, Latino 19%, White 43%). All had low incomes. Surveys consisted of multiple-choice items and open-ended responses. Results The study found that one size does not fit all when it comes to ICT training and support for older adults. While connection to devices and services and tech support led to a degree of ICT adoption, the newly learned skills did not always lead to expanded device usage. The readily available tech support training and support do not guarantee service utilization, as success with tech services is related to one’s pre-existing ICT competence. Discussion The study concludes that customized training based on individuals’ skills rather than age is needed. Tech support training should start by understanding an individual’s interests and incorporate tech education to help users identify a wide range of existing and emerging online services that can meet their needs. Service organizations should consider including an assessment of ICT access, use, and skills into their standard intake protocols to ensure effective service delivery.